Scaup Aythya marila numbers and the Cockle Cardium edule fishery on the Solway Firth: are they related? - Quinn, J L; Still, L; Carrier, M C; Kirby, J S; Lambdon, P (Wildfowl, 1996)
This paper describes the changes in numbers of Scaup wintering on the Solway Firth, Scotland and offers an explanation for variation in their numbers and, in recent years, their distribution. Scaup occurred on the Solway in ’thousands’ in the 1950s, but from 1961 to 1986, numbers rarely exceeded 1,000. The initial decline coincided exactly with the sudden large increase in numbers on the Firth of Forth. Commercial cockling began on the Solway in 1987 and with it came a large increase in the numbers of Scaup. There was a significant correlation between the size of the Cockle harvest and Scaup numbers from 1986 to 1993. Changes in the distribution of Scaup within the Solway between 1991 and 1994 were related to the distribution of cockling effort. It is suggested that Scaup have taken advantage of the increased feeding opportunities provided by the large amounts of Cockles rejected (due to their small size or damage) by the cockling industry. When commercial cockling was banned on the Solway in June 1992, Scaup declined and many of those remaining moved to an area of Mussel beds which was considered, historically, to be their main feeding area on the Solway.